2014
DOI: 10.1039/c4an01438c
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of DNA through a fluorescence biosensor based on click chemistry

Abstract: A simple, sensitive and selective fluorescence biosensor for determination of DNA using CuS particles based on click chemistry is reported. Biotin-modified capture DNA was modified on Streptavidin MagneSphere Paramagnetic Particles (PMPs) and hybridized with target DNA (hepatitis B virus DNA had been chosen as an example), then bound target DNA was hybridized with DNA-CuS particles and formed a sandwich like structure. CuS particles on the sandwich structures can be destroyed by acid to form Cu(II), and Cu(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…At 5 MHz field (70 V rms /cm plus 1.5 V DC /cm), while the fluorescence intensity of anti-mouse-IgG does not rise above background level, the respective intensity for PSA is enhanced ~7.5-fold. Based on linear rise of fluorescence intensity versus logarithm of biomarker concentration 33,34 , this suggests ~10 3 -fold concentration enrichment in ~30 s, as validated previously 22 . The nDEP dispersion (Fig.…”
Section: Resultssupporting
confidence: 73%
“…At 5 MHz field (70 V rms /cm plus 1.5 V DC /cm), while the fluorescence intensity of anti-mouse-IgG does not rise above background level, the respective intensity for PSA is enhanced ~7.5-fold. Based on linear rise of fluorescence intensity versus logarithm of biomarker concentration 33,34 , this suggests ~10 3 -fold concentration enrichment in ~30 s, as validated previously 22 . The nDEP dispersion (Fig.…”
Section: Resultssupporting
confidence: 73%
“…To quantify viral DNA, biotin-labeled capture DNA was immobilized onto Streptavidin MagneSphere Paramagnetic Particles and hybridized with hepatitis B viral DNA, followed by hybridizing the target DNA with DNA-CuS particles to form a sandwich like structure (Fig. 3c) (Yue et al, 2014). Then, the CuS particles were acidized to form Cu(II) and Fig.…”
Section: Diagnosis Of Viral Infectionmentioning
confidence: 99%
“…later reduced to Cu(I) by sodium ascorbate. The resulting Cu(I) catalyzed the formation of a fluorescent 1,2,3-triazole compound between a weakly fluorescent 3-azido-7-hydroxycoumarin and propargyl alcohol (Yue et al, 2014). It was found that there was a direct linear relationship between the fluorescence intensity and the target DNA concentrations in the range of 0.1-100 nM, and the detection limit is 0.04 nM (Yue et al, 2014).…”
Section: Diagnosis Of Viral Infectionmentioning
confidence: 99%
See 2 more Smart Citations